Analytical solutions for electronic states in three‐dimensional semiconductor quantum rings. Issue 9 (7th June 2013) - Vänskä, O.; Kira, M.; Koch, S. W.; Tittonen, I.; Ulrich, Sven M.; Jetter, Michael; Michler, Peter
Abstract We study single‐particle electronic states of a threedimensional semiconductor quantum ring. Starting from the envelope‐function theory, we formulate a fully analytical model for single‐particle wave functions and confinement energies of charge carriers. The approximative harmonic‐oscillator model is found to be in excellent agreement with numerical results. The model is a powerful tool in practical calculations when there is a need to go beyond single particle properties to more demanding many‐body effects. (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)